Balancing Cost and Performance: Cloud Optimization Strategies for Financial Institutions - Subramanian, Shriya; Naik, Ananda (Journal of Global Economy, Business and Finance, 2025)
This paper explores cloud optimization strategies in financial institutions, emphasizing the balance between cost efficiency and performance. The study discusses methods such as resource utilization, cost driver identification, and performance monitoring systems that enable institutions to optimize their cloud infrastructure. The findings suggest that effective cloud optimization can significantly enhance operational efficiency and reduce costs, making it an essential strategy for financial institutions.